2019
DOI: 10.1007/s40519-019-00750-4
|View full text |Cite
|
Sign up to set email alerts
|

Body composition parameters can better predict body size dissatisfaction than body mass index in children and adolescents

Abstract: Purpose Recent studies suggest that body mass index is not a reliable enough measurement for body composition in individuals, particularly in older and younger people. However, most research on body image has used the body mass index (BMI) as a physiological predictor of body satisfaction, particularly in children. The aim of this study was to investigate whether body composition is a better predictor of body size dissatisfaction in children than BMI. Methods This is a cross-sectional study. Healthy children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…An inverse relationship was observed with skeletal muscle mass. These data are in line with the literature [ 21 , 47 , 48 , 49 ] supporting that people with a higher BMI experience a more negative body image and, thus, require special attention.…”
Section: Discussionsupporting
confidence: 92%
“…An inverse relationship was observed with skeletal muscle mass. These data are in line with the literature [ 21 , 47 , 48 , 49 ] supporting that people with a higher BMI experience a more negative body image and, thus, require special attention.…”
Section: Discussionsupporting
confidence: 92%
“…Since for both age ranges the presence of outliers was smaller than the permitted threshold, the tool is suitable to evaluate the body parameters of the two age groups (25) . Santos et al, using bioimpedance to investigate the body composition of 547 children and adolescents (aged 5 to 19 years) in Brazilian schools, also found high percentages of eutrophic individuals (59 %), followed by overweight (21•1 %) and obese students (19•9 %) (39) . Recent studies have reported an ongoing increase in the rates of overweight and obese people throughout the world.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, since obesity might influence the mental disorders, we explored the potential effect of body composition on this issue, using the measure of dual-energy X-ray absorptiometry (DEXA), a previously validated measure in pediatric populations. Compared to BMI, body composition measures could better predict body size dissatisfaction in children and adolescents ( 53 ). Certain limitations should also be paid attention.…”
Section: Discussionmentioning
confidence: 99%